2013
DOI: 10.1371/journal.pone.0062248
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the Plasmidome within Enterococcus faecalis Isolated from Marginal Periodontitis Patients in Norway

Abstract: The present study aimed to identify and characterize plasmids in a national collection of oral Enterococcus faecalis (n = 106) isolated from patients with marginal periodontitis. Plasmid replicon typing was performed by multiplex-PCR and sequencing with specific primers for 18 rep-families and 1 unique sequence. Additional plasmid analysis by S1-PFGE was performed for comparison. Totally 120 plasmid replicon amplicons of seven rep-families were identified in 93 E. faecalis strains, e.g. rep9 (prototype pCF10),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 33 publications
5
17
3
Order By: Relevance
“…Methods of direct detection by PCR using degenerate primers have been reported for IncP-1, IncP-7, and IncP-9 plasmids from environmental samples (Dealtry et al, 2014 ) and for plasmids of different MOB families (Alvarado et al, 2012 ). Many plasmids have been identified from environmental samples, including the human gut, by metagenomic analyses (Elsaied et al, 2011 ; Kristiansson et al, 2011 ; Zhang et al, 2011 ; Brolund et al, 2013 ; Song et al, 2013 ). Brown Kav et al characterized the overall plasmid population in the bovine rumen (termed rumen plasmidomes) by sequencing the extracted circular plasmids (Brown Kav et al, 2012 , 2013 ).…”
Section: Methods For Plasmid Isolation and Identificationmentioning
confidence: 99%
“…Methods of direct detection by PCR using degenerate primers have been reported for IncP-1, IncP-7, and IncP-9 plasmids from environmental samples (Dealtry et al, 2014 ) and for plasmids of different MOB families (Alvarado et al, 2012 ). Many plasmids have been identified from environmental samples, including the human gut, by metagenomic analyses (Elsaied et al, 2011 ; Kristiansson et al, 2011 ; Zhang et al, 2011 ; Brolund et al, 2013 ; Song et al, 2013 ). Brown Kav et al characterized the overall plasmid population in the bovine rumen (termed rumen plasmidomes) by sequencing the extracted circular plasmids (Brown Kav et al, 2012 , 2013 ).…”
Section: Methods For Plasmid Isolation and Identificationmentioning
confidence: 99%
“…Furthermore, both microbiome and plasmidome analyses have been performed for the bovine rumen [ 15 ]. Plasmidome analysis in particular has been carried out for ESBL in Escherichia coli [ 16 ] and various plasmids in Enterococcus faecalis [ 17 ]. Module-based phage network analysis has been demonstrated to suggest a reticulate representation of evolutionary and functional relationships between phage genomes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…These plasmids have been shown to play a pivotal role in genetic exchange among the gut microbiota (Palmer et al, ). However, the role of pheromone‐responsive conjugative plasmids in the oral cavity is not well‐studied, despite numerous reports of the isolation of enterococci from oral sites (Delboni, Gomes, Francisco, Teixeira, & Drake, ; Sedgley, Lennan, & Clewell, ) and the recovery of enterococcal cells carrying determinants from the pheromone‐responsive plasmid pAM373 associated with periodontal (Song et al, ) and unsuccessfully treated endodontic (Barbosa‐Ribeiro et al, ) lesions. Oral metagenomic sequencing studies show a broad distribution of antibiotic resistance genes even without antibiotic selective pressure (Sukumar, Roberts, Martin, & Adler, ).…”
Section: Discussionmentioning
confidence: 99%
“…Active cAM373 pheromones induce a pAM373 mating response which includes the expression of enterococcal surface‐linked aggregation substance (AS) protein that facilitates bacterial co‐aggregation as well as DNA transfer functions that allow conjugative transfer of pAM373 and co‐resident plasmids into pAM373‐free recipient cells. Such intergeneric communication may be of biological and clinical relevance in the oral cavity since enterococci, including those that carry pAM373 derivatives (Barbosa‐Ribeiro et al, ; Song, Sun, Mikalsen, Roberts, & Sundsfjord, ) are recovered from the same niches occupied by oral streptococci (Komiyama et al, ). Functional and genetic studies have confirmed that in S. gordonii the signal peptide of the CamG lipoprotein is processed at the amino terminus by the zinc metalloprotease Eep and at the carboxyl terminus by the peptidase LspA to produce the active pheromone peptide s.g.cAM373 (SVFILAA) (Vickerman et al, ) .…”
Section: Introductionmentioning
confidence: 99%